Design of Sequence-Specific DNA Binding Molecules for DNA Methyltransferase Inhibition - Kang, JeenJoo S. (American Chemical Society, 2014)
[Image: see text] The CpG dyad, an important genomic feature in DNA methylation and transcriptional regulation, is an attractive target for small molecules. To assess the utility of minor groove binding oligomers for CpG recognition, we screened a small library of hairpin pyrrole-imidazole polyamides targeting the sequence 5′-CGCG-3′ and assessed their sequence specificity using an unbiased next-generation sequencing assay. Our findings indicate that hairpin polyamide of sequence PyImβIm-γ-PyImβIm (1), previously identified as a high affinity 5′-CGCG-3′ binder, favors 5′-GCGC-3′ in an unanticipated reverse binding orientation. Replacement of one β alanine with Py to afford PyImPyIm-γ-PyImβIm (3) restores the preference for 5′-CGCG-3′ binding in a forward orientation. The minor groove binding hairpin 3 inhibits DNA methyltransferase activity in the major groove at its target site more effectively than 1, providing a molecular basis for design of sequence-specific antagonists of CpG methylation.